Carotenoids in green corn grains after post-emergence herbicide application - Rios, Sara de Almeida; Paes, Maria Cristina Dias; Karam, Décio; Borém, Aluízio; Cardoso, Wilton Soares (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the efect of post-emergence herbicide application on carotenoid content in green corn grains. A completely randomized design was used, with five treatments – no application; foramsulfuron + iodosulfuron-methyl-sodium (40 g ha-1); nicosulfuron (20 g ha-1); mesotrione (120 g ha-1) and tembotrione (100 g ha-1) –, and two replicates. The grains were evaluated in terms of lutein, zeaxanthin, beta-cryptoxanthin, alpha-carotene and beta-carotene, pro-vitamin A carotenoids, total carotenoid contents, and percentage of lutein, zeaxanthin and pro-vitamin A carotenoids. Tembotrione and nicosulfuron herbicides did not cause deleterious effects on total carotenoids or fractions with pro-vitamin A activity.